Does Characterizing Global Running Pattern Help to Prescribe Individualized Strength Training in Recreational Runners? - Patoz, Aurélien; Breine, Bastiaan; Thouvenot, Adrien; Mourot, Laurent; Gindre, Cyrille; Lussiana, Thibault (Frontiers in Physiology, 2021)
This study aimed to determine if concurrent endurance and strength training that matches the global running pattern would be more effective in increasing running economy (RE) than non-matched training. The global running pattern of 37 recreational runners was determined using the Volodalen® method as being aerial (AER) or terrestrial (TER). Strength training consisted of endurance running training and either plyometric (PLY) or dynamic weight training (DWT). Runners were randomly assigned to a matched (n=18; DWT for TER, PLY for AER) or non-matched (n=19; DWT for AER, PLY for TER) 8-week concurrent training program. RE, maximal oxygen uptake ((V) ̇O_2max) and peak treadmill speed at V ̇O_2max (PTS) were measured before and after the training intervention. None of the tested performance related variables depicted a significant group effect or interaction effect between training and grouping (p≥0.436). However, a significant increase in RE, V ̇O_2max, and PTS (p≤0.003) was found after the training intervention. No difference in number of responders between matched and non-matched groups was observed for any of the performance related variables (p≥0.248). In recreational runners, prescribing PLT or DWT according to the global running pattern of individuals, in addition to endurance training, did not lead to greater improvements in RE.